DAKWAH NABI ISA: Perspektif Pendidikan Aqidah - ., Mappasiara (Inspiratif Pendidikan, 2019)
One but three persons (Trinity) are the views of Christians from the Al-Mulkaniyyah, An-Nusturiyyah, and Ya’kubiah groups. They are the ones who declare the trinity and also they say that the Godhead is united between Allah, Jesus, and Mary. This is what they call the three elements. Indeed, those who say that Allah is the Lord who created the heavens and the earth and all of these contents are composed of three persons. They are infidels and threatened by Allah SWT with the torment of hellfire in the hereafter. The substance of the Prophet’s preaching is the teachings of monotheism, that God is one and there is no god but Allah.